Economic threshold of Heliothis virescens in three Tobacco varieties from Cuba - PIEDRA-DÍAZ, FELICIA; PALACIOS-VALDÉZ, FELICITA; LINARES-YERA, NORMA; VÁZQUEZ-RODRÍGUEZ, MIGUEL (Revista Colombiana de Entomología, 1999)
During the years 1986-1989 several investigations were carried out in order to determine the economic threshold of H. virescens (tobacco budworm ) in the tobacco crop on different varieties, being. Pinar del Rio (var.Criollo), La Habana (var. Corojo without any sun covering), and Villa Clara (var. Pelo de Oro) the provinces where the work was conducted. was determine(’ the appropriate threshold taking into consideration the damage, infestation index, losses, and protection measures against this pest. The threshold of 9.3: 6.35 and 9.2 were obtained for each the ahoy mentioned varieties, respectively. It should be considere(’ these economic thresholds after transplantation to establish the control measures and to avoid the losses.